Phenolic Compounds and Antioxidant Activity of Methanolic Extracts of Moosir (allium hirtifolium boiss) Bulbs - Amir Siahpoosh; Sogol Sohangir (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2013)
Objective: Moosir is an endemic plant from Liliaceae that’s growth in iran. Its medicinal effects that are noted in traditional medicine antirhomatism, appetizer, stomachic, digestive, anti-worm and parasite and anti-impotency.Subjects and methods: Moosir bulbs were collected from Aligoodarz in Lorestan. Methanolic extracts was prepared from bulbs by maceration method. Antioxidant activity of extract was evaluated by five antioxidant assays: FRAP, DPPH, TEAC, Radical hydroxyl scavenging activity and Iron chelating capacity. Total phenolic content, flavonoids and oligomeric proanthocyanidins of two extracts were also determined.Results: Results obtained in the present study revealed that moosir was effective in DPPH (IC50: 0.59 mg/ml), TEAC (TEAC Value: 2.71 mMol Trolox/100 g DW, 6 min), FRAP (EC1: 0.11 mg/ml), deoxyribose (IC50: 0.125 mg/ml), Total polyphenol, flavonoids and oligomeric proanthocyanidin contents and iron chelating IC50 were 78.66 mg Tannic Acid equivalents/g DE, 2.65 mg Rutin equivalents/g DE, 0.861 mg cyanidin equivalents/g DE and 0.62 mg/ml. Conclusion: The results obtained in the present study demonstrated that methanolic extract of moosir have good antioxidnat effects and it can be used for the treatment of diseases related to radicals or as food additives